An Investigation of Gel Polymer Electrolytes Plasticized with Imidazolium Ionic Liquid - Radzir, N.N.M.; Hanifah, S.A.; Ahmad, A.; Hassan, N.H. (Asian Journal of Chemistry, 2015)
Gel polymer electrolytes were developed by adding room temperature ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethyl-sulfonyl)imide in poly(glycidyl methacrylate) matrix with 30 wt. % of lithium bis(trifluoromethylsulfonyl)imide salt. The physical properties of the transparent and non-volatile membranes were investigated. The interactions between polymer, ionic liquid and salt were studied using Fourier transformation infra-red. Besides, the thermal properties were investigated using differential scanning calorimetry, whereas the ionic conductivity of the membranes was looked into using electrochemical impedance spectroscopy. The results showed insignificant interactions between oxygen atoms in polymer backbone and ionic dopants. Nevertheless, it was observed that a decrease in the temperature for glass transition led to an increase in the conductivity of ionic up to 2.66 × 10-6 S cm-1 and a decrease in the activation energy for PGMA-30 wt. % of LiTFSI-BmimTFSI mixtures in the membrane.